DETERMINANTS OF PROFITABILITY AT BANK MEGA SYARIAH FROM 2015 to 2021 - Bahtiar, Eko; Amin, Al (Journal Of Islamic Ekonomic and Business, 2023)
ABSTRACT The aim of this research is to analyze the influence of the operational efficiency ratio (BOPO), capital adequacy level (CAR), non-performing financing (NPF), and liquidity (FDR) on the profitability of Bank Mega Syariah in Indonesia in 2015-2021. This research is quantitative research. The data source used in this research is secondary data, namely the annual financial report from Bank Mega Syariah obtained via the OJK website. The research results show that the NPF variable: tcount (0.395) < ttable (4.302) and with a significance level of 0.731 > 0.05, it means Ho. accepted and H1 rejected. Independent variable (NPF) partially. does not have a significant effect on the dependent variable (ROA). BOPO variable: The results show that Ho is accepted and H1 is rejected, because tcount (- 4.661) < ttable (4.302), and the significance level is 0.043 > 0.05. The dependent variable (ROA) is not significantly influenced by BOPO. CAR variable: Ho is accepted and H1 is rejected, because tcount (3.068) < ttable (4.302) with a significance level of 0.092 > 0.05. The dependent variable (ROA) is not partially influenced by CAR. FDR variable: tcount value 2.664 < ttable value 4.302, and significance level 0.117 > ttable value 0.05 indicating that Ho is accepted and H1 is rejected. The dependent variable (ROA) is not partially influenced by the independent variable (FDR).